Preparation method of pseudo-boehmite
By using a combination of inorganic aluminum salt and polymer aluminum chloride, combined with ammonium bicarbonate, urea and PEG600-800 composite pore reamer, the gradient heating drying method was used to prepare the phthalinated alumina, which solved the problem of low specific surface area and gum-soluble properties in the prior art, and achieved the effect of high specific surface area and high gum-soluble index.
Patent Information
- Application Number
- CN202510059003.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The specific surface area and gum-soluble properties of the existing double-aluminum method are low, which affects its crystallinity, sintering performance and stability.
The combination of inorganic aluminum salt and polymer aluminum chloride was used, combined with ammonium bicarbonate, urea and PEG600-800 composite pore reamer, and the pseudothic aluminite was prepared by gradient heating and drying.
The specific surface area and gumification index of phthalite were effectively improved, and its composite performance was improved, ensuring that the specific surface area was 445.8-475.2m2/g and the gumification index was 98.2-99.6%.
Smart Images

Figure BDA0005242284330000081
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of pseudo-boehmite with high colloidal properties and high specific surface area, belonging to the field of catalytic carrier materials. Background Art
[0002] The finished product of pseudo-boehmite is a white, non-toxic, odorless powder. It is a type of hydrated aluminum oxide with an uncertain composition and a spatial network structure. Therefore, it has a large specific surface area, pore volume and average pore size, and its microstructure is relatively simple. Pseudo-boehmite is widely used in plastics, petrochemicals, papermaking, construction and environmental protection industries. It is not only an important carrier for the preparation of activated alumina, but also an important binder in catalyst synthesis. It has a very wide range of applications in the petrochemical industry. The synthesis processes of pseudo-boehmite include: alcohol aluminum method, hydrothermal method, double aluminum method, carbonization method, alkali method, acid method, acid-base method, etc. The double aluminum method
[73] uses aluminum salts and aluminates as raw materials. Al 3+ and AlO 2- The pseudo-boehmite is prepared by reaction. The preparation operation of this method is simple, the reaction conditions are mild, the product purity is high, no impurities such as gibbsite are generated, and the raw materials are cheap and easy to obtain. However, the pseudo-boehmite prepared by the double aluminum method has a slightly lower crystallinity than that of other methods, especially after adding a pore-enlarging agent, the crystallinity and peptization performance are significantly reduced. The crystallinity has an important influence on the specific surface area, pore volume, peptization performance, sintering performance and stability of pseudo-boehmite. Therefore, it is of great significance to develop a method for preparing pseudo-boehmite with high specific surface area and high sol performance. Summary of the invention
[0003] The invention provides a method for preparing pseudo-boehmite, which solves the problems of low specific surface area and peptization performance of the pseudo-boehmite prepared by the existing double aluminum method.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0005] A method for preparing pseudo-boehmite comprises the following steps:
[0006] (1) dissolving an inorganic aluminum salt and polyaluminum chloride in water to prepare an aluminum salt solution;
[0007] (2) dissolving aluminate in water, and then adding a composite pore-enlarging agent to prepare a composite aluminate solution;
[0008] (3) adding the aluminate composite solution dropwise to the aluminum salt solution to form a gel, stirring while adding dropwise, and controlling the gelling temperature at 60-70°C;
[0009] (4) adjusting the pH of the reaction solution to 9.0 with aqueous ammonia, controlling the temperature at 85-90° C., and stirring for aging;
[0010] (5) After aging, the product was collected, filtered, and washed with water 2-3 times;
[0011] (6) Drying is performed by a gradient heating method to obtain pseudo-boehmite.
[0012] Furthermore, preferably: the inorganic aluminum salt is aluminum sulfate, aluminum chloride and aluminum nitrate, the weight ratio of the inorganic aluminum salt to polyaluminum chloride is 99.8:0.2, and the concentration of the aluminum salt solution is 0.1-0.6 mol / L.
[0013] Furthermore, preferably: the aluminate is sodium aluminate or potassium aluminate, and the concentration of the aluminate composite solution is 0.1-0.6 mol / L, calculated as aluminate.
[0014] Furthermore, preferably: the composite pore-enlarging agent includes ammonium bicarbonate, urea and PEG600-800, and the weight ratio of ammonium bicarbonate: urea: PEG600-800 is 5:4:1.
[0015] Furthermore, preferably, the amount of the composite pore-enlarging agent added is 1-3% of the weight of the aluminate.
[0016] Furthermore, preferably: in the step (3), the dropping speed is 1-10 mL / min, and the stirring speed is 400-600 r / min.
[0017] Furthermore, preferably: the stirring speed in the step (4) is 400-600 r / min.
[0018] Further, preferably: the gradient temperature is increased at 2°C / min to 70°C and kept warm for 20-30min; then increased at 1°C / min to 90°C and kept warm for 1-2h; finally increased at 3-5°C / min to 110°C and kept warm for 1-2h.
[0019] Furthermore, preferably: a silane coupling agent and a surfactant are also added in the obtained step (2), the weight ratio of the silane coupling agent to the surfactant is 3:1, and the amount of the silane coupling agent added is 0.05-0.1% of the weight of the aluminate.
[0020] Furthermore, preferably: the surfactant is an anionic surfactant.
[0021] Beneficial effects of the present invention:
[0022] The aluminum salt of the invention adopts a combination of inorganic aluminum salt and polyaluminum chloride, and uses ammonium bicarbonate, urea and PEG600-800 as a pore-enlarging agent. The drying adopts a gradient temperature increase, which can effectively increase the specific surface area of pseudo-boehmite and improve the peptization index, so that it has good composite performance, and the specific surface area is 445.8-475.2m 2 / g, and the peptization index is 98.2-99.6%. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] A method for preparing pseudo-boehmite comprises the following steps:
[0026] (1) Weigh 14.97 g of aluminum sulfate and 0.03 g of polyaluminum chloride (polyaluminum chloride has an aluminum oxide content of 30% and a basicity of 50) and dissolve them in deionized water. Stir at 400 r / min for 20 min to prepare a 0.5 mol / L aluminum sulfate solution.
[0027] (2) 10 g of aluminate was dissolved in deionized water, stirred at 400 r / min for 20 min to prepare a 0.5 mol / L aluminum salt solution, and then 0.2 g of a composite pore-enlarging agent was added, stirred at 400 r / min for 20 min to prepare a composite aluminate solution; the composite pore-enlarging agent was ammonium bicarbonate: urea: PEG600 in a ratio of 5:4:1;
[0028] (3) adding the aluminate composite solution dropwise to the aluminum salt solution to form a gel, stirring while adding dropwise, controlling the gelling temperature at 65°C, the dropping speed at 5 mL / min, and the stirring speed at 500 r / min;
[0029] (4) Adjust the pH of the reaction solution to 9.0 with aqueous ammonia, control the temperature at 85°C, stir at 500 r / min, and age for 1.5 h;
[0030] (5) After aging, the product was collected, filtered, and washed with deionized water three times;
[0031] (6) Drying is performed by a gradient heating method to obtain pseudo-boehmite. The temperature is increased to 70°C at a rate of 2°C / min and kept at this temperature for 30 minutes; then the temperature is increased to 90°C at a rate of 1°C / min and kept at this temperature for 1 hour; finally, the temperature is increased to 110°C at a rate of 5°C / min and kept at this temperature for 2 hours.
[0032] Comparative Example 1
[0033] The method is basically the same as Example 1, except that: (1) 15 g of aluminum sulfate was weighed and dissolved in deionized water at 400 r / min for 20 min to prepare a 0.5 mol / L aluminum sulfate solution.
[0034] Comparative Example 2
[0035] It is basically the same as Example 1, except that ammonium bicarbonate is used as the pore expanding agent.
[0036] Comparative Example 3
[0037] It is basically the same as Example 1, except that urea is used as the pore expanding agent.
[0038] Comparative Example 4
[0039] It is basically the same as Example 1, except that the pore expanding agent is a composite pore expanding agent of ammonium bicarbonate and PEG600, and the ratio of ammonium bicarbonate:PEG600 is 9:1.
[0040] Comparative Example 5
[0041] It is basically the same as Example 1, except that the pore expanding agent is a composite pore expanding agent of urea and PEG600, and the ratio of urea:PEG600 is 9:1.
[0042] Comparative Example 6
[0043] The method is basically the same as Example 1, except that the drying is carried out by direct heating: the temperature is increased gradually at 2°C / min to 110°C and kept warm for 3h.
[0044] Comparative Example 7
[0045] The method is basically the same as Example 1, except that the drying is carried out by direct heating: the temperature is increased gradually at 5°C / min to 110°C and kept warm for 3h.
[0046] The prepared products were subjected to performance tests, as follows:
[0047] The pore structure of the sample was tested using a physical adsorption instrument. About 0.1 g of the sample to be tested was weighed into a specific sample tube and degassed at 300 °C for 8 h under a vacuum environment to remove water and impurities. The adsorption-desorption analysis was carried out under 77K liquid nitrogen temperature conditions, and the specific surface area, pore volume and average pore size were calculated using the BET and BJH equations, respectively.
[0048] The peptization index measurement method is as follows:
[0049] (1) Place m1g of the test sample in a muffle furnace, heat it to 800°C at a rate of 10°C / min, keep it at that temperature for 2h, cool it naturally to room temperature, and weigh m2g. The alumina mass fraction of the sample is w = m2 / m1×100%.
[0050] (2) Accurately weigh 10.00 g of sample into a 100 mL beaker, add (w×100-10) g of deionized water to prepare a 10% (in terms of alumina) pseudo-boehmite suspension; add (10×w×0.16) g of concentrated HNO3 (mass fraction 65%) and stir with an electromagnetic stirrer for 10 min; transfer the formed colloidal solution to a 200 mL plastic test tube, centrifuge it in a centrifuge at 3500 r / min for 10 min, take the supernatant and place it in a 100 mL crucible, dry it in a 120°C oven for 12 h, then heat it to 800°C in a muffle furnace at 10°C / min, keep it for 2 h, cool it naturally to room temperature, and weigh m3g. The peptization index of the sample is (m3 / 10w)×100%.
[0051] The specific measurement results are shown in Table 1.
[0052] Table 1 Performance measurement of pseudo-boehmite prepared in different embodiments
[0053] <![CDATA[Specific surface area / (m 2 / g)]]> <![CDATA[Pore volume / (cm 3 / g)]]> Average pore size / (nm) Peptization index / % Example 1 452.8 0.51 4.03 98.7 Comparative Example 1 471.6 0.53 4.37 88.6 Comparative Example 2 486.2 0.57 4.49 85.7 Comparative Example 3 465.8 0.98 8.67 86.8 Comparative Example 4 461.2 0.54 6.85 91.6 Comparative Example 5 459.6 0.62 7.24 93.1 Comparative Example 6 456.9 0.48 3.69 86.1 Comparative Example 7 456.2 0.81 8.64 85.4
[0054] As can be seen from Table 1, the pseudo-boehmite of the present invention has a high surface area and a high peptization index. The aluminum salt of the present invention adopts a combination of an inorganic aluminum salt and polyaluminum chloride. By adding a small amount of polyaluminum chloride, the aluminum ions in the polyaluminum chloride can serve as nucleation centers to promote the nucleation and growth of pseudo-boehmite crystals. This added aluminum source helps to improve the orderliness of the crystals, thereby improving the crystallinity. Polyaluminum chloride can improve the dispersibility of pseudo-boehmite particles and reduce the agglomeration phenomenon between particles. Good dispersibility helps to transport materials during crystal growth, thereby facilitating the improvement of crystallinity. At the same time, by adding polyaluminum chloride, pseudo-boehmite can be promoted to form a porous structure and increase the specific surface area. Compared with Comparative Example 1, without adding polyaluminum chloride, the specific surface area is slightly increased, but its peptization index is significantly reduced, with a reduction rate of 9.76%.
[0055] Comparative Examples 2-5 investigate the effects of different pore-enlarging agents on pseudo-boehmite. It can be seen that the use of ammonium bicarbonate or urea alone as a pore-enlarging agent can effectively increase the specific surface area, but will cause a significant decrease in the peptization index, which has a significant impact on the performance of the pseudo-boehmite. The present invention uses a composite pore-enlarging agent, which effectively ensures that the pseudo-boehmite has a large specific surface area while having a good peptization index. Compared with Comparative Examples 2 and 3, the specific surface area is reduced by 6.87% and 2.79%, respectively, and the peptization index is increased by 15.16% and 13.71%.
[0056] The present invention adopts ammonium bicarbonate, urea and PEG600-800 as a pore-enlarging agent. The decomposition speed and temperature of ammonium bicarbonate and urea are different. During gradient drying, the gases generated during decomposition act synergistically to promote the formation of more pores and increase the specific surface area of the material. At the same time, PEG600-800 is adsorbed on the surface of pseudo-boehmite particles and guides the growth of crystals as a template, which helps the crystals grow in a specific direction, thereby improving the crystallinity; at the same time, it helps to stabilize these pore structures and prevent the collapse of pores during heat treatment. The ammonia generated by ammonium bicarbonate and urea can also adjust the pH value of the solution and provide a suitable environment for the growth of crystals. The surface activity of PEG600-800 can reduce the agglomeration of pseudo-boehmite particles, maintain the stability of the particles, and is conducive to maintaining a high crystallinity during the crystal growth process.
[0057] In the process of preparing pseudo-boehmite by the double aluminum method, the composite pore expander of ammonium bicarbonate, urea and PEG600-800 promotes each other to improve the specific surface area and crystallinity of pseudo-boehmite by synergistically creating pore structure, improving the crystal growth environment and controlling agglomeration, thereby effectively improving the peptization index.
[0058] Comparative Examples 6 and 7 investigate the effects of different drying methods on pseudo-boehmite, and it can be seen that the drying method has a significant effect on the peptization index of pseudo-boehmite. Gradient temperature drying can provide a relatively mild and controllable drying environment, which is conducive to the growth of pseudo-boehmite crystals. In the early stage of drying, the lower temperature helps to maintain the hydroxyl groups on the surface of pseudo-boehmite, which are necessary conditions for crystal growth. As the temperature gradually increases, water gradually migrates from the inside of the crystal to the surface and evaporates. This process helps to repair crystal defects and improve the crystal structure.
[0059] Gradient temperature drying can reduce the drying stress caused by rapid drying, which may damage the crystal structure and reduce the crystallinity. By gradually increasing the temperature, the internal moisture has enough time to migrate to the surface, reducing the internal stress during the drying process and protecting the crystal structure. Gradient temperature drying helps to reduce the agglomeration of particles during the drying process, and at the same time can reduce the powdering caused by too fast drying rate. Gradient temperature drying helps to maintain the integrity of the particles.
[0060] Gradient temperature drying has a positive effect on the crystallinity of pseudo-boehmite. It can provide an environment conducive to crystal growth, reduce stress during drying, control phase transformation, and reduce agglomeration and pulverization, thereby improving the crystallinity of pseudo-boehmite.
[0061] Example 2
[0062] A method for preparing pseudo-boehmite comprises the following steps:
[0063] (1) Weigh 14.97 g of aluminum sulfate and 0.03 g (polyaluminum chloride with a content of 30% aluminum oxide and a basicity of 50) and dissolve them in deionized water. Stir at 400 r / min for 20 min to prepare a 0.1 mol / L aluminum sulfate solution.
[0064] (2) 10 g of aluminate was dissolved in deionized water, stirred at 400 r / min for 20 min to prepare a 0.1 mol / L aluminum salt solution, and then 0.1 g of a composite pore-enlarging agent was added, stirred at 400 r / min for 20 min to prepare a composite aluminate solution; the composite pore-enlarging agent was ammonium bicarbonate: urea: PEG700 in a ratio of 5:4:1;
[0065] (3) adding the aluminate composite solution dropwise to the aluminum salt solution to form a gel, stirring while adding dropwise, controlling the gelling temperature at 60°C, the dropping speed at 10 mL / min, and the stirring speed at 400 r / min;
[0066] (4) Adjust the pH of the reaction solution to 9.0 with aqueous ammonia, control the temperature at 85°C, stir at 400 r / min, and age for 1 h;
[0067] (5) After aging, the product was collected, filtered, and washed twice with deionized water;
[0068] (6) Drying is performed by a gradient heating method to obtain pseudo-boehmite. The temperature is increased to 70°C at a rate of 2°C / min and kept at this temperature for 20 minutes; then the temperature is increased to 90°C at a rate of 1°C / min and kept at this temperature for 1.5 hours; finally, the temperature is increased to 110°C at a rate of 3°C / min and kept at this temperature for 2 hours.
[0069] Example 3
[0070] A method for preparing pseudo-boehmite comprises the following steps:
[0071] (1) Weigh 14.97 g of aluminum sulfate and 0.03 g of polyaluminum chloride (polyaluminum chloride has an aluminum oxide content of 30% and a basicity of 50) and dissolve them in deionized water. Stir at 400 r / min for 20 min to prepare a 0.6 mol / L aluminum sulfate solution.
[0072] (2) 10 g of aluminate was dissolved in deionized water, stirred at 400 r / min for 20 min to prepare a 0.6 mol / L aluminum salt solution, and then 0.3 g of a composite pore-enlarging agent was added, stirred at 400 r / min for 20 min to prepare a composite aluminate solution; the composite pore-enlarging agent was ammonium bicarbonate: urea: PEG600 in a ratio of 5:4:1;
[0073] (3) adding the aluminate composite solution dropwise to the aluminum salt solution to form a gel, stirring while adding dropwise, controlling the gelling temperature at 70°C, the dropping speed at 1 mL / min, and the stirring speed at 600 r / min;
[0074] (4) Adjust the pH of the reaction solution to 9.0 with aqueous ammonia, control the temperature at 90°C, stir at 600 r / min, and age for 1 h;
[0075] (5) After aging, the product was collected, filtered, and washed with deionized water three times;
[0076] (6) Drying is performed by a gradient heating method to obtain pseudo-boehmite. The temperature is increased to 70°C at a rate of 2°C / min and kept at this temperature for 30 minutes; then the temperature is increased to 90°C at a rate of 1°C / min and kept at this temperature for 1.5 hours; finally, the temperature is increased to 110°C at a rate of 5°C / min and kept at this temperature for 1 hour.
[0077] Example 4
[0078] A method for preparing pseudo-boehmite comprises the following steps:
[0079] (1) Weigh 14.97 g of aluminum sulfate and 0.03 g of polyaluminum chloride (polyaluminum chloride has an aluminum oxide content of 30% and a basicity of 50) and dissolve them in deionized water. Stir at 400 r / min for 20 min to prepare a 0.4 mol / L aluminum sulfate solution.
[0080] (2) 10 g of aluminate was dissolved in deionized water, stirred at 400 r / min for 20 min to prepare a 0.4 mol / L aluminum salt solution, and then 0.2 g of a composite pore-enlarging agent was added, stirred at 400 r / min for 20 min to prepare a composite aluminate solution; the composite pore-enlarging agent was ammonium bicarbonate: urea: PEG600 in a ratio of 5:4:1;
[0081] (3) adding the aluminate composite solution dropwise to the aluminum salt solution to form a gel, stirring while adding dropwise, controlling the gelling temperature at 65°C, the dropping speed at 8 mL / min, and the stirring speed at 500 r / min;
[0082] (4) Adjust the pH of the reaction solution to 9.0 with aqueous ammonia, control the temperature at 85°C, stir at 500 r / min, and age for 1.5 h;
[0083] (5) After aging, the product was collected, filtered, and washed with deionized water three times;
[0084] (6) Drying is performed by a gradient heating method to obtain pseudo-boehmite. The temperature is increased to 70°C at a rate of 2°C / min and kept at this temperature for 30 minutes; then the temperature is increased to 90°C at a rate of 1°C / min and kept at this temperature for 1 hour; finally, the temperature is increased to 110°C at a rate of 5°C / min and kept at this temperature for 2 hours.
[0085] Example 5
[0086] The method is basically the same as Example 1, except that: a silane coupling agent and a surfactant are further added in the obtained step (2), the weight ratio of the silane coupling agent to the surfactant is 3:1, and the amount of the silane coupling agent added is 0.05% of the weight of the aluminate. The silane coupling agent is A151, and the surfactant is sodium dodecyl sulfate.
[0087] The physical and chemical properties of the pseudo-boehmite prepared in Examples 2-5 were measured, as shown in Table 2.
[0088] Table 2 Performance measurement of pseudo-boehmite prepared in different embodiments
[0089]
[0090] As can be seen from Table 2, the pseudo-boehmite prepared by the present invention has good physical and chemical properties. As can be seen from Example 5, the present invention adopts a silane coupling agent and a surfactant compound. The silane coupling agent has an amphoteric structure, one end of which can chemically react with the hydroxyl group on the surface of the pseudo-boehmite, and the other end is an organic functional group that is compatible with organic molecules. When the silane coupling agent acts on the surface of the pseudo-boehmite particles, the hydrogen bonding between the particles can be reduced and the tendency to agglomerate can be reduced; the surfactant contains two parts, hydrophilic and hydrophobic, and can form micelles in the solution, and adsorb on the surface of the particles with the help of its hydrophilic group, thereby stabilizing the particles and preventing agglomeration. The two work together to effectively improve the dispersibility of the pseudo-boehmite particles and provide good conditions for the uniform nucleation and growth of crystals.
[0091] At the same time, the silane coupling agent can serve as the nucleation center of crystal growth by forming an ordered organic layer on the surface of pseudo-boehmite particles, guiding the crystal to grow in a certain lattice orientation. Surfactant: By reducing the surface tension, it can increase the solubility of pseudo-boehmite in the solution, which is conducive to the formation of new crystal nuclei. Their combined action can effectively promote the rate and number of crystal nucleation, help to form a uniform and ordered crystal structure, and then improve the crystallinity of pseudo-boehmite, and then improve the peptization index of pseudo-boehmite.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing pseudo-boehmite, characterized in that: The following steps are involved: (1) dissolving an inorganic aluminum salt and polyaluminum chloride in water to prepare an aluminum salt solution; (2) dissolving aluminate in water, and then adding a composite pore-enlarging agent to prepare a composite aluminate solution; (3) adding the aluminate composite solution dropwise to the aluminum salt solution to form a gel, stirring while adding dropwise, and controlling the gelling temperature at 60-70°C; (4) Adjust the pH of the reaction solution to 9.0 with aqueous ammonia, control the temperature at 85-90°C, and stir for aging for 1-2 hours; (5) After aging, the product was collected, filtered, and washed with water 2-3 times; (6) Drying is performed by a gradient heating method to obtain pseudo-boehmite.
2. The preparation method according to claim 1, characterized in that: The inorganic aluminum salt is aluminum sulfate, aluminum chloride and aluminum nitrate, the weight ratio of the inorganic aluminum salt to polyaluminum chloride is 99.8:0.2, and the concentration of the aluminum salt solution is 0.1-0.6 mol / L.
3. The preparation method according to claim 1, characterized in that: The aluminate is sodium aluminate or potassium aluminate. The concentration of the aluminate composite solution is 0.1-0.6 mol / L based on the aluminate.
4. The preparation method according to claim 1, characterized in that: The composite pore-enlarging agent comprises ammonium bicarbonate, urea and PEG600-800, and the weight ratio of ammonium bicarbonate:urea:PEG600-800 is 5:4:
1.
5. The preparation method according to claim 1, characterized in that: The added amount of the composite pore-enlarging agent is 1-3% of the weight of the aluminate.
6. The preparation method according to claim 1, characterized in that: In the step (3), the dropping speed is 1-10 mL / min and the stirring speed is 400-600 r / min.
7. The preparation method according to claim 1, characterized in that: The stirring speed in the step (4) is 400-600 r / min.
8. The preparation method according to claim 1, characterized in that: The gradient temperature is increased at 2°C / min to 70°C and kept warm for 20-30min; then increased at 1°C / min to 90°C and kept warm for 1-2h; finally increased at 3-5°C / min to 110°C and kept warm for 1-2h.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The obtained step (2) further adds a silane coupling agent and a surfactant, the weight ratio of the silane coupling agent to the surfactant is 3:1, and the added amount of the silane coupling agent is 0.05-0.1% of the weight of the aluminate.
10. The preparation method according to claim 9, characterized in that: The surfactant is an anionic surfactant.
Citation Information
Cited By
Preparation method of high-purity pseudo-boehmite
CN121872420A
Phosphorus modified high specific surface area large pore volume pseudo-boehmite and preparation method thereof
CN122789422A